Measurement of the concentration of lead and cadmium in some cosmetics sold in the markets of Nalut city (مجلة العلوم الشاملة, 2025)
Cosmetics are a mixture of chemical compounds derived from natural or artificial sources, and they do not contain environmental pollutants such as heavy metals, which may pose health risk when exposed to them. Due to the scarcity of local studies on this topic, in addition to the known toxicity of lead (Pb) and cadmium (CD) Especially with daily use, this research was conducted to determine the concentration of these two ingredients in facial cosmetics (lipstick, eyeshadow, eyeliner).30 samples were collected from the markets of Nalut City, and selected based on color, price, country of origin, and source of production. The samples were sent to the Delta Scientific Laboratory for analysis using the Atomic Absorber-Graphite Furnace (GF-AAS).The results of the analysis showed trace concentrations of lead and cadmium in all samples, and were within the limits allowed according to the guidelines of the U.S. FDA,  The World Health Organization (WHO), and Health Canada, and  there were significant relation between cosmetic type, price and manufacture of lipstick and eyeshadow and lead concentration ,whereas no relation between source of kohl production and lead and cadmium concentration.